2010
DOI: 10.2174/156720110793360649
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Extemporaneously Manufactured Topical Gels Containing Aceclofenac on Inflammation and Hyperalgesia in Rats

Abstract: The systemic use of non-steroidal anti-inflammatory drugs (NSAIDs) which act by inhibiting cyclooxygenase (COX) is severely hampered by gastric and peptic ulcers. The topical delivery of NSAIDs has the advantages of avoiding gastric and peptic ulcers and delivering the drug to the inflammation site. Importance of aceclofenac as a new generational NSAID has inspired the development of topical dosage forms. This mode of administration may help to avoid typical side effects of NSAIDs associated with oral and syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In creams, owing to their biphasic nature, partitioning of the drug occurs in two phases, resulting in slower release of drug; while in the case of gels, the drug diffusion occurred through the aqueous phase and hence they offer a greater drug diffusion and release. [78]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In creams, owing to their biphasic nature, partitioning of the drug occurs in two phases, resulting in slower release of drug; while in the case of gels, the drug diffusion occurred through the aqueous phase and hence they offer a greater drug diffusion and release. [78]…”
Section: Discussionmentioning
confidence: 99%
“…In each of the formulations, NF and C. longa was incorporated at 5 and 2% w/w concentration in the base with trituration using geometric dilution procedure to get a homogeneous mass. [78910]…”
Section: Methodsmentioning
confidence: 99%
“…Further studies infer that silver nanoparticles are nontoxic to human dermal fibroblast and inhibit fungal growth. 116 120,121 The best formulation was formulated to topical gel using carbopol as a gelling agent and evaluated for its pH, physical appearance, spreadibility, viscosity, and homogeneity. The result concludes that aceclofenac loaded nanostructured lipid carrier could be a potential drug delivery system for topical applications.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…31 In addition, much greater tissue concentrations can be achieved compared with systemic delivery 32 and, in preclinical models, topical application of NSAIDs can attenuate inflammatory hypersensitivity. 33 Pre-clinical work has also demonstrated that pro-inflammatory prostaglandins (e.g. PGE2) can sensitize nociceptors, produce pain-like behaviour when injected peripherally 34 -37 and are over-expressed in hypersensitive tissue areas after inflammation.…”
Section: Prostanoidsmentioning
confidence: 99%